PENGARUH PERMAINAN MATCHING GAME BERBASIS VISUAL STUDIO CODE TERHADAP KEMAMPUAN MEMAHAMI KOSAKTA BAHASA INGGRIS ANAK - Syifa Abaska; Rismareni Pransiska (STKIP Subang, 2026)
This research is motivated by the lack of development of English vocabulary comprehension skills of early childhood children, especially in recognizing, understanding meaning, and matching vocabulary with appropriate images. In addition, the use of less interactive learning media causes low motivation and involvement of children in the learning process. Therefore, innovation of learning media that is interesting and appropriate to the characteristics of early childhood is needed. This study aims to test the effect of Visual Studio Code-based matching games on the ability to understand English vocabulary of children in Hangtuah Padang Kindergarten. This study uses a quantitative approach with a quasi-experimental method. The research subjects were 20 children in group B consisting of two classes, namely class B2 as the experimental class and class B1 as the control class, each consisting of 10 children. The data collection technique used a test consisting of 4 statement items. Data analysis was carried out through normality test, homogeneity test, and hypothesis test (independent sample t-test) with the help of SPSS version 29.0. The results of the study showed a significant difference between the ability to understand English vocabulary of children in the experimental class and the control class with a significance value of 0.004 <0.05. The average ability score of children in the experimental class experienced a higher increase than the control class after being given treatment. Thus, it can be concluded that the Visual Studio Code-based matching game is effective in improving the ability to understand English vocabulary of early childhood children